Rare cases of classical Hurler-Scheie syndrome - Saluja, Tajindra Singh; Satoskar, Sujata; Vaidya, Aniket Uday; Dhameliya, Mayur D. (International Journal of Contemporary Pediatrics, 2016)
Mucopolysaccharidosis (MPS) are the rare inherited metabolic disorders typified by deficiency of lysosomal enzymes necessary for glycosaminoglycan (GAG) metabolism. The inadequate metabolism of GAGs results in its accumulation causing multi-organ dysfunction. Of the different MPSs, MPS-I is caused by deficiency of lysosomal enzyme α-L-iduronidase, and inherited in an autosomal recessive manner. The severity of the disease presentation varies widely and classically three phenotypes, Hurler syndrome (MPS IH), Hurler-Scheie syndrome (MPS-IH/S) and Scheie syndrome (MPS-IS) are described. This case report depicts MPS-IH/S in two consecutive male siblings with typical clinical and radiological features that helped in establishing the diagnosis.